Optimization Design of Heavy Type Vehicle Wet Clutch based on Improved Metropolis Algorithm - Chen Feng (Jixie chuandong)
To the problems of wet clutch designs of heavy type vehicle are more conservative,the high production cost and so on. Through the adaptive function transformation to determine initial temperature,combining with the success- failure method and the variable metric method,the traditional Metropolis algorithm is improved,and the improved method is applied to the optimization design of wet clutch of heavy type vehicle.Finally,the model after optimization are verified by the theoretical and experimental.